2021
DOI: 10.48550/arxiv.2111.09750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The self-consistent field iteration for p-spectral clustering

Abstract: The self-consistent field (SCF) iteration, combined with its variants, is one of the most widely used algorithms in quantum chemistry. We propose a procedure to adapt the SCF iteration for the p-Laplacian eigenproblem, which is an important problem in the field of unsupervised learning. We formulate the p-Laplacian eigenproblem as a type of nonlinear eigenproblem with one eigenvector nonlinearity , which then allows us to adapt the SCF iteration for its solution after the application of suitable regularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, similar to the original Euclidean p-Laplacian and graph linear Laplacian, the p-Laplacian on graphs has some important relations to Cheeger cut problem and shortest path problem on graphs. Just as the Laplacian matrix which has been successfully used in diverse areas, the graph p-Laplacian has been also widely used in various applications, including spectral clustering [10,32,55,56], data and image processing problems, semi-supervised learning and unsupervised learning [35,55,56]. Much recent work has shown that algorithms based on the graph p-Laplacian perform better than classical algorithms based on the linear Laplacian in solving these practical problems in image science.…”
Section: Introductionmentioning
confidence: 99%
“…For example, similar to the original Euclidean p-Laplacian and graph linear Laplacian, the p-Laplacian on graphs has some important relations to Cheeger cut problem and shortest path problem on graphs. Just as the Laplacian matrix which has been successfully used in diverse areas, the graph p-Laplacian has been also widely used in various applications, including spectral clustering [10,32,55,56], data and image processing problems, semi-supervised learning and unsupervised learning [35,55,56]. Much recent work has shown that algorithms based on the graph p-Laplacian perform better than classical algorithms based on the linear Laplacian in solving these practical problems in image science.…”
Section: Introductionmentioning
confidence: 99%
“…For example, similar to the original Euclidean p-Laplacian and graph linear Laplacian, the p-Laplacian on graphs has some important relations to Cheeger cut problem and shortest path problem on graphs. Just as the Laplacian matrix which has been successfully used in diverse areas, the graph p-Laplacian has been also widely used in various applications, including spectral clustering [7,16,30,31], data and image processing problems, semi-supervised learning and unsupervised learning [27,30,31]. Much recent work has shown that algorithms based on the graph p-Laplacian perform better than classical algorithms based on the linear Laplacian in solving these practical problems in image science.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly interesting that this type of nonlinear Laplacian operator appears in many settings. For example, in the graph case, if f = id and g(x) = |x| p−1 sign(x), then L boils down to the graph p-Laplacian operator [16,23,42,52]. Exponential-and logarithmicbased choices of f and g give rise to nonlinear Laplacians used to model chemical reactions [37,53] as well as to model consensus dynamics and opinion formation in hypergraphs [35].…”
mentioning
confidence: 99%